2022
DOI: 10.1007/s00464-021-08999-6
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble deep learning for the prediction of proficiency at a virtual simulator for robot-assisted surgery

Abstract: Background Artificial intelligence (AI) has the potential to enhance patient safety in surgery, and all its aspects, including education and training, will derive considerable benefit from AI. In the present study, deep-learning models were used to predict the rates of proficiency acquisition in robot-assisted surgery (RAS), thereby providing surgical programs directors information on the levels of the innate ability of trainees to facilitate the implementation of flexible personalized training. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Moglia et al utilized ensemble deep learning neural network models to identify at an early stage the acquisition rates of surgical technical proficiency of trainees. [29] Hung et al [31] previously used robotic surgical APMs during RARP and clinicopathological data to accurately predict continence after RARP, achieving a C-index of 0.6 via a DL model (DeepSurv) [31]. The study demonstrated that surgeons with more efficient APMs achieved higher continence rates at 3 and 6 months post-RARP.…”
Section: Intraoperative Assessmentmentioning
confidence: 99%
“…Moglia et al utilized ensemble deep learning neural network models to identify at an early stage the acquisition rates of surgical technical proficiency of trainees. [29] Hung et al [31] previously used robotic surgical APMs during RARP and clinicopathological data to accurately predict continence after RARP, achieving a C-index of 0.6 via a DL model (DeepSurv) [31]. The study demonstrated that surgeons with more efficient APMs achieved higher continence rates at 3 and 6 months post-RARP.…”
Section: Intraoperative Assessmentmentioning
confidence: 99%
“…Moglia et al used deep learning to develop a model to predict the proficiency of medical students in a surgical simulator based on their training data. Subsequently, they used the model to predict proficiency from simulator data of untrained medical students with an accuracy rate of >80% ( 27 ). Excessive stress experienced by surgeons can negatively affect their surgical procedures, and Zheng et al developed a deep-learning model to detect, in real time, the movements of surgical procedures in which surgeons appear to be under stress.…”
Section: Analysis Of Laparoscopic Surgery Video Using Deep Learningmentioning
confidence: 99%
“…Although it will still require a long time before the development of a fully autonomous surgical system, the development of a hybrid system may be realized in the near future. Therefore, it is necessary to discuss ethical issues related to autonomous surgical systems ( 27 ).…”
Section: Autonomous Surgical Robotsmentioning
confidence: 99%
See 2 more Smart Citations